RANCANG BANGUN APLIKASI DOCUMENT MANAGEMENT SYSTEM PADA BAGIAN KEPEGAWAIAN DI PERUSAHAAN DAERAH PASAR SURYA SURABAYA - Supriyanto, Supriyanto; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The company Solar Market Area (PDPS) is a company engaged in the field of community service in the city of Surabaya. In the process of its business, coupled with PDPS administrative staffing processes. Document management administration process is divided into six staffing processes. In those processes, currently experiencing difficulty in managing documents. This is because the process of shipping, receiving, storage, search, and document approval is done manually. It also results in the process of pengirimanan, search, and document storage became longer, the difficulty in providing additional information, security, and permissions settings for the document.